INTEGRASI NILAI KEBANGSAAN MELALUI LAGU DARI SABANG SAMPAI MERAUKE DI KELAS 3 MI AL FALAH NGAWI - M. Ali Imron Abdul Aziz; M. Abdul Rozaq K.; Istiadah; Aisyah Latifatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the process of integrating national values and to analyze the effectiveness of the national song “Dari Sabang Sampai Merauke” as a medium for character development among third-grade students at MI Al Falah Ngawi. The importance of instilling unity and patriotism from an early age requires innovative learning approaches that are appropriate to the context of primary education. The method used is a descriptive qualitative approach with data collected from previous references. This research method is intended to provide an in-depth description of how national values are integrated through music. The song serves as a symbol of Indonesian unity by illustrating the natural beauty and cultural diversity stretching from Sabang to Merauke.